Multifunctional Porous Pavement Prototype for Urban Pluvial Flood Protection: Preliminarily Findings on Contribution of Attitudes to Acceptance Willingness Toward Proposed Scientific and Engineering Solutions - Snezana Svetozarevic,; Vladana Rajakovic Ognjanovic,; Branislava Lekic,; Aleksandar Savic, (International Journal of Integrated Engineering, 2024)
Rapid urbanization and climate change correlate with an increase in frequency of flood events, globally. For many cities worldwide pluvial floods bring significant risk. Permeable/pervious paving (PePav), as an essential sustainable urban drainage technique, is one of the key environmental solutions for urban flooding. Waste and recycled materials in the construction industry for PePav production comply with the principles of circular economy and sustainable development. The influence of the human factor is well recognized in efforts to apply those solutions and make them self-sustainable. The preliminary results show that younger female students and students with lower family monthly income are prone to express more positive attitudes toward PePav generally. Students from different study groups (Departments of Psychology, Hydraulic and Environmental Engineering, and Construction Project Management) show significantly different attitudes toward PePav. Statistical models indicate that the PePav acceptance willingness can be predicted with moderate accuracy by knowing attitudes toward PePav and personal experience in construction. The contributions of the fact that someone's close person has been affected by a flood may vary depending on the type of PePav scientific and engineering solutions.